Η παρουσία του κινηματογράφου στα ελληνικά λογοτεχνικά περιοδικά των μεταπολεμικών και μεταπολιτευτικών χρόνων (1949-2009). Παρουσίαση του ομώνυμου ερευνητικού προγράμματος - Γαραντούδης Δήμητρα Ραζάκη Νάντια Φραγκούλη, Ευριπίδης (Σύγκριση/Comparaison/Comparison, 2021)
The presence of cinema in Greek literary magazines in the second half of the twentieth century (1949-2009). Presentation of the research program This paper describes the results of the research program ‘The presence of cinema in Greek literary magazines in the second half of the twentieth century (1949-2009)’. This research project, funded by ESPA, resulted in the creation of a digital database that will become available online within the year 2021. This study presents the structure and content of the created data base, along with an indicative case study. The case study focuses on the theme cinemagoing as a part of everyday life, analysing text samples from a wide variety of genres found in the literary magazines of the second half of the twentieth century.